Allantoin attenuates deficits of behavioural and motor nerve conduction in an animal model of cisplatin‐induced neurotoxicity in rats. Issue 2 (1st July 2019) - N S, Vindya; Mohamad, Aqib; Razdan, Rema
Abstract: Background: The aim of the present study was to evaluate the neuroprotective effect of allantoin in cisplatin‐induced toxicity in rats. Methods: Adult male Wistar rats weighing 160‐200 g were used. Neuropathy was induced by injecting cisplatin (2 mg/kg, ip, twice a week for 6 weeks) and the rats were concurrently treated with allantoin (200 and 400 mg/kg, po) for 8 weeks. At the end of the study, body weight and hemogram were measured. Behavioural tests were performed, including tests for cold and hot hyperalgesia, motor co‐ordination, locomotor activity, mechano‐tactile allodynia and mechanical hyperalgesia. The rats were then sacrificed and sciatic nerve conduction velocity was determined. The antioxidant enzyme and nitric oxide levels in sciatic nerve homogenates were measured. Results: In this study, allantoin restored the motor nerve conduction velocity deficits induced by cisplatin, and the allantoin‐treated rats showed improvement in cold and thermal hyperalgesia, mechano‐tactile allodynia, and mechanical hyperalgesia. Allantoin treatment also improved the rats' hematological status, increasing haemoglobin, platelet and RBC counts compared to the cisplatin‐treated group. Allantoin treatment also mitigated the functional abnormalities seen in the cisplatin neuropathy group, protecting neurons from the neurotoxic effects of cisplatin. Conclusion: Allantoin shows promise for use as an adjuvant drug in cancer treatment to protect against cisplatin‐induced neuropathy.